Practices and perceptions in hamstring training for injury prevention and enhancement of athletic performance: a qualitative analysis - Ross, S.; Ripley, N. J.; Comfort, P. (International Journal of Sports Science & Coaching, 2025)
Hamstring strain injuries (HSIs) remain a prevalent issue across sports, despite extensive research. Previously, the current authors have reported practices and perceptions of training for the mitigation of HSIs, however such practices are highly nuanced. In this study, the authors utilised semi-structured interviews to further understand applied practitioner perceptions and identify how evidence is translated into practice. Twelve practitioners (one physiotherapist and eleven strength and conditioning [S&C] coaches including one dual accredited S&C coach and physiotherapist) working in a range of sporting disciplines were interviewed across six broad categories of questioning (practitioner profile, job role challenges, resistance training, high-speed running training, athlete testing and monitoring and views on contemporary research). Thematic analyses highlighted key challenges relating to limited time spent with athletes, fixture schedules and planning of training across the broader multidisciplinary team (MDT) as well as strategies to deal with such challenges such as micro-dosing of the resistance training stimulus, utilisation of isometric exercise during fixture congestion periods. However, analyses also highlighted some areas of research that are not well translated into practice such as recommendations for the use of low-volumes of the Nordic hamstring exercise to elicit positive adaptations in strength and repeated bout effects and minimal effective dosages for resistance training. The findings of the study highlight the need for continued athlete and practitioner education, better communication and planning in the MDT and further research into minimum effective dosages to elicit strength adaptation in elite level athletes.